2014
DOI: 10.1139/cjfr-2014-0038
|View full text |Cite
|
Sign up to set email alerts
|

Beech bark disease: spatial patterns of thicket formation and disease spread in an aftermath forest in the northeastern United States

Abstract: Beech bark disease (BBD) has affected the composition, structure, and function of forests containing a significant proportion of American beech (Fagus grandifolia Ehrh.) across North America. BBD spread has been investigated at landscape and regional scales, but few studies have examined spatial patterns of disease severity and spread within stands where forest management mitigation measures can be implemented. We analyzed changes in forest composition between 1985 and 2009 and fine-scale spatial patterns of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…Also our results in accordance with Kelly et al (2008) indicate that the disease severity of the charcoal canker in the oak forest is not randomly distributed. Therefore, based on the results obtained, we can acknowledge that in the earlier epidemic, the dead trees are strongly clustered at large scales (800 m) (Giencke et al 2014). The results of the relationship between the severity of the disease symptom classifications of the dead oak trees using the paired quadrat covariance (PQC) showed that the trees with great damage caused by the disease have a strong association with dead trees so that healthy trees or with low severity of the disease were far from dead trees (Kot et al 1996;Havel et al 2002;Kelly et al 2008;Meentemeyer et al 2008).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Also our results in accordance with Kelly et al (2008) indicate that the disease severity of the charcoal canker in the oak forest is not randomly distributed. Therefore, based on the results obtained, we can acknowledge that in the earlier epidemic, the dead trees are strongly clustered at large scales (800 m) (Giencke et al 2014). The results of the relationship between the severity of the disease symptom classifications of the dead oak trees using the paired quadrat covariance (PQC) showed that the trees with great damage caused by the disease have a strong association with dead trees so that healthy trees or with low severity of the disease were far from dead trees (Kot et al 1996;Havel et al 2002;Kelly et al 2008;Meentemeyer et al 2008).…”
Section: Discussionmentioning
confidence: 63%
“…In this regard, Kelly et al (2008) investigated the spatial pattern dynamics of the oak mortality affected by sudden oak death and the results of their research showed that in the early process of the disease invasion, dead trees were strongly clustered at smaller scales and after three years this clustering was less pronounced. Giencke et al (2014) implemented the bivariate point pattern analysis to examine the spatial patterns of beech thicket formation and the beech bark disease spread. Their results indicated that the disease severity of beech saplings was highest in close proximity to highly cankered canopy beech trees.…”
mentioning
confidence: 99%
“…If a dense understory layer of small beeches formed beneath large beech trees, which might be expected given beech's dispersal limitation, seedling establishment patterns, and extreme shade tolerance, these subcanopy beeches would be poised to quickly reclaim dominance after canopy disturbance. And this may be what happens in beech stands with abundant sprout regeneration, where small stems are positively correlated with adult conspecifics (Takahashi et al 2010;Giencke et al 2014). As such, the CNDD that we have documented in the understory of a mature undisturbed forest may be critical for the increase in diversity that occurs post-disturbance, at least in stands where advance regeneration is primarily of seed origin.…”
Section: Discussionmentioning
confidence: 86%
“…Sprouting is also more common on harsher sites (farther north and/ or higher elevation) and where beech roots have been injured by management operations or natural factors (Held 1983;Tubbs and Houston 1990;Cleavitt et al 2008;Takahashi et al 2010). In addition, many American beech stands are heavily impacted by beech bark disease, which leads to tremendous root sprouting and the formation of "beech thickets" that are clustered around dead and dying adults (Wagner et al 2010;Giencke et al 2014). While beech bark disease has been heavily impacting beech stands in the northern US for decades (Busby and Canham 2011;Giencke et al 2014), it remains absent from most of the southeast, with damage in this region documented only in higher elevations in the Appalachian mountains (Virginia Department of Forestry 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation